Exploring Children’s Preferences in Water Transportation: A Bibliometric Analysis - Andri Irfan Rifai; Siti Tasyah; Yusra Aulia Sari; Joewono Prasetijo (Engineering Proceedings, 2025)
The transportation choices of children commuting to school significantly impact their quality of life and safety. This study focuses on the unique aspect of water transportation, which is prevalent in various regions worldwide. Through a comprehensive analysis of 1000 research papers using Publish or Perish and VOSViewer, we explore the critical factors influencing children’s preferences and experiences with water transport. The findings highlight that understanding these preferences is essential for developing safer and more efficient modes of water-based transportation. By addressing the specific challenges school-aged children face, this research aims to inform the design and implementation of improved water transport solutions, ultimately enhancing their well-being and security. This study underscores the importance of tailored transportation strategies in creating a safer and more supportive environment for children navigating their daily commutes.